2022
DOI: 10.1177/02654075221131902
|View full text |Cite
|
Sign up to set email alerts
|

Perceived partner support and post-traumatic symptoms after an acute cardiac event:A longitudinal study

Abstract: Objective Cardiac disease induced post-traumatic stress symptoms (CDI-PTSS) have been associated with negative consequences for patients’ mental and physical health. Identifying risk factors as well as potential buffers is necessary for understanding the development and maintenance of CDI-PTSS. The current study focused on the mediating and moderating role played by patients’ perceptions of their partners’ ways of providing support (active engagement, overprotection, and protective buffering) in the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…Patients whose partners engaged in a protective buffering coping style (i.e., tendency to deny and to hide worries from the patient; Coyne and Smith, 1994 ), presented higher depression levels but only when perceiving their partners' buffering coping style as low, thus not protective (Vilchinsky et al, 2011 ). In a recent publication, we also detected that patients' perceived partners' protective buffering was associated with their cardiac-disease-induced posttraumatic stress symptoms (CDI-PTSS) over time (George-Levi et al, 2022 ). Interestingly, patients' CDI-PTSS was associated with distress and fear of illness progression among their partners (Eisenberg et al, 2022 ); and cardiac patients' partners' depression was found to associate with lower marital satisfaction of both patient and partner (Dekel et al, 2013 ).…”
Section: It Takes Two To Develop Negative Clinical Outcomesmentioning
confidence: 86%
“…Patients whose partners engaged in a protective buffering coping style (i.e., tendency to deny and to hide worries from the patient; Coyne and Smith, 1994 ), presented higher depression levels but only when perceiving their partners' buffering coping style as low, thus not protective (Vilchinsky et al, 2011 ). In a recent publication, we also detected that patients' perceived partners' protective buffering was associated with their cardiac-disease-induced posttraumatic stress symptoms (CDI-PTSS) over time (George-Levi et al, 2022 ). Interestingly, patients' CDI-PTSS was associated with distress and fear of illness progression among their partners (Eisenberg et al, 2022 ); and cardiac patients' partners' depression was found to associate with lower marital satisfaction of both patient and partner (Dekel et al, 2013 ).…”
Section: It Takes Two To Develop Negative Clinical Outcomesmentioning
confidence: 86%
“…On the one hand, partners might show intense psychological distress due to caregiving activities also affecting the balance between given and received support in the couple [8][9][10]. On the other hand, supportive partner behaviors could have a positive effect on patient psychological reaction [11,12], and on cardiac self-management outcomes, for example, by increasing the levels of medication adherence [13] and patient engagement [13,14]. These dynamics of interdependence and mutual influence between partners could be explained by the concept of dyadic coping (DC; [15,16]), i.e., the couple's level of ability to cope with daily or major stress situations together.…”
Section: Introductionmentioning
confidence: 99%